Gratitude and Its Relationship with Students’ Psychological Well-Being and Happiness - Dorkas Ping, Bilong; Ida Juliana, Hutasuhut; Mohamad Azhari, Abu Bakar; Nurul, Wardhani (2021)
This study examines gratitude among undergraduate students of a public university in Malaysia and its relationship with psychological well-being and happiness. This study took 149 samples randomly from 235 undergraduate students who were asked to participate in answering Gratitude Questionnaire-6, Ryff's Scale of Psychological Well Being, and Subjective Happiness Scale. Correlation analysis shows a positive relationship between gratitude and students' psychological well-being and happiness. This study supports the previous studies that practicing gratitude is a positive way to enhance students' healthy psychological well-being and happiness in their life. This study recommends the university management to take consideration to cultivate gratitude practice embedded in the curriculum or in the extracurricular activities.